English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories
0

(3x^-2)^-3 the 3 is raised to the whole problem and it is division
(5y^-9)

2006-10-25 14:16:03 · 2 answers · asked by Jeff W 1 in Science & Mathematics Mathematics

2 answers

Just guessing, but is it :

[3x^(-2)]^(-3) / [5y^(-9)] ?

Working on the numerator, each part can be raised to the power of (-3).
After that, remember that in general, A^(-B) = 1 / A^B.

[3x^(-2)]^(-3)

= 3^(-3) * [x^(-2)]^(-3)

= (1 / 3^3) * x^6

= x^6 / 27.

For the denominator, 5y^(-9) = 5 / y^9.

Now, numerator / denominator = (x^6 / 27) / (5 / y^9)

= (x^6 / 27) * (y^9 / 5)

= x^6 * y^9 / 135, as the final simplified answer.

2006-10-25 14:55:36 · answer #1 · answered by falzoon 7 · 0 0

what do you want to do.
solve what?? you did not write an equation, and whatever is written is not clear at all what you mean

2006-10-25 21:27:32 · answer #2 · answered by locuaz 7 · 0 1

fedest.com, questions and answers